2022
DOI: 10.1177/2156759x221076846
|View full text |Cite
|
Sign up to set email alerts
|

Applying for RAMP Using a Cohort Model: Results of a Multilevel Case Study

Abstract: School counselors across the United States are implementing comprehensive school counseling programs, such as those following the American School Counselor Association (ASCA) National Model. ASCA awards a designation honoring exemplary school counseling programs: Recognized ASCA Model Program (RAMP). Although a growing number of studies have examined RAMP status through survey methods and student outcomes, the need remains to understand RAMP through the lens of each school’s unique context and experience. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…To date, numerous studies have examined RAMP and student outcomes with mixed results (for a full review, please see our first article in this series, Goodman-Scott et al, 2021). For instance, using archival data in Indiana, Wilkerson et al (2013) found that RAMP-designated schools across elementary, middle, and high school levels had higher test scores than the control group of non-RAMP schools; in particular, findings were significant for elementary level math and English/language arts scores.…”
Section: Implementation Factors Related To Comprehensive School Couns...mentioning
confidence: 99%
“…To date, numerous studies have examined RAMP and student outcomes with mixed results (for a full review, please see our first article in this series, Goodman-Scott et al, 2021). For instance, using archival data in Indiana, Wilkerson et al (2013) found that RAMP-designated schools across elementary, middle, and high school levels had higher test scores than the control group of non-RAMP schools; in particular, findings were significant for elementary level math and English/language arts scores.…”
Section: Implementation Factors Related To Comprehensive School Couns...mentioning
confidence: 99%
“…Similarly, Hilts et al (2019) found, through a quantitative examination of school counselors’ perceptions of barriers when establishing a comprehensive school counseling program, that participants experienced a lack of stakeholder support, time constraints, inappropriate duty assignments, and a lack of confidence. In a two-part study, Goodman-Scott et al (2022) and Taylor et al (2022) explored a school counseling regional cohort group as they prepared for RAMP over a 2-year period. In the first study, Goodman-Scott et al (2022) employed a participatory descriptive case study of one RAMP-seeking district multilevel cohort group (i.e., school counselors, district-level coordinator, facilitators, and state department of education liaisons; N = 24), whereby the RAMP process was facilitated through a district–university partnership.…”
Section: Introductionmentioning
confidence: 99%
“…In a two-part study, Goodman-Scott et al (2022) and Taylor et al (2022) explored a school counseling regional cohort group as they prepared for RAMP over a 2-year period. In the first study, Goodman-Scott et al (2022) employed a participatory descriptive case study of one RAMP-seeking district multilevel cohort group (i.e., school counselors, district-level coordinator, facilitators, and state department of education liaisons; N = 24), whereby the RAMP process was facilitated through a district–university partnership. The findings from this study revealed participants’ enthusiasm and concerns with the RAMP process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations